Semi-automatic volumetric tumor segmentation for hepatocellular carcinoma: Comparison between C-arm Cone Beam Computed Tomography and MRI - Tacher, Vania (2013)
RATIONALE AND OBJECTIVES: To evaluate the precision and reproducibility of a semi-automatic tumor segmentation software in measuring tumor volume of hepatocellular-carcinoma–(HCC) before the first trans-arterial chemo-embolization–(TACE) on contrast-enhancement magnetic-resonance-imaging–(CE-MRI) and intra-procedural dual-phase C-arm cone-beam computed-tomography–(DP-CBCT) images. MATERIALS AND METHODS: 19HCCs were targeted in 19patients(one per patient) who underwent baseline diagnostic CE-MRI and an intra-procedural DP-CBCT. The images were obtained from CE-MRI–(arterial-phase of an intra-venous contrast medium injection) and DP-CBCT–(delayed-phase of an intra-arterial contrast medium injection) before the actual embolization. Three readers measured tumor volumes using a semi-automatic 3D-volumetric segmentation software which used a region-growing method employing non-Euclidean radial basis functions. Segmentation time and spatial position were recorded. The tumor volume measurements between images sets were compared using linear-regression and Student t-test, and evaluated with Intraclass-Correlation analysis–(ICC). The inter-rater Dice Similarity Coefficient–(DSC) accessed the segmentation spatial localization. RESULTS: All 19 HCCs were analyzed. On CE-MRI and DP-CBCT examinations respectively, A) the mean segmented tumor volumes was 87±8cm(3)[2–873] and 92±10cm(3)[1–954], with no statistical difference of segmented volumes by readers of each tumor between the two imaging modalities and the mean time required for segmentation was 66±45seconds [21–173] and 85±34seconds[17–214] (p=0.19), B),the ICCs were 0.99 and 0.974, showing a strong correlation among readers, and C) the inter-rater DSCs showed a good to excellent inter-user agreement on the spatial localization of the tumor segmentation–(0.70±0.07 and 0.74±0.05,p=0.07). CONCLUSION: This study shows a strong correlation, precision and reproducibility of semi-automatic tumor segmentation software in measuring tumor volume on CE-MRI and DP-CBCT images. The use of the segmentation software on DP-CBCT and CE-MRI can be a valuable and highly accurate tool to measure the volume of hepatic tumors.